2010
DOI: 10.1111/j.1095-8649.2010.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

A major fish stranding caused by a natural hypoxic event in a shallow bay of the eastern South Pacific Ocean

Abstract: A massive beaching and mortality of fishes occurred in Coliumo Bay, a shallow bay located along the coast of the eastern South Pacific Ocean on 3 January 2008. This stranding was a consequence of an abrupt decrease in the dissolved oxygen concentration throughout the whole water column, due to the effect of intense upwelling along the coast off central-southern Chile. The main objectives of this study were: (1) to characterize taxonomically and biologically the fish species assemblage present in this beaching;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…On the third day of this upwelling-hypoxic event, DO below 0.5 ml O 2 l À1 were detected and a massive die-off/stranding of marine organisms was reported, affecting zooplankton, mollusks, crustaceans and fishes. Fish species were strongly impacted by this hypoxic event, but previous fish species richness and half of the previous abundance were recovered during the three months following the event (Hernández-Miranda et al, 2010). This is in agreement with the Pearson and Rosenberg general model for community response to hypoxia for organic enrichment.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…On the third day of this upwelling-hypoxic event, DO below 0.5 ml O 2 l À1 were detected and a massive die-off/stranding of marine organisms was reported, affecting zooplankton, mollusks, crustaceans and fishes. Fish species were strongly impacted by this hypoxic event, but previous fish species richness and half of the previous abundance were recovered during the three months following the event (Hernández-Miranda et al, 2010). This is in agreement with the Pearson and Rosenberg general model for community response to hypoxia for organic enrichment.…”
Section: Introductionsupporting
confidence: 83%
“…We provide a more detailed description of the oceanographical dynamics of the hypoxic event in January 2008, complementing and expanding a previous description (Hernández-Miranda et al, 2010). We then assess two main hypotheses regarding the response to hypoxia of epibenthic macrofauna in Coliumo Bay.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it is important to also understand how such environments may affect fed species, as these may not be optimal for fish growth. In some upwelling areas, like the Benguela current or the Humboldt current, hypoxia events occur frequently and this can be detrimental for cultivated species (Ekau et al, 2010;Hernández-Miranda et al, 2010.…”
Section: Environmental Benefits and Limitationsmentioning
confidence: 99%
“…An intense event of natural hypoxia in January 2008 affected the entire resident community of shallow Coliumo Bay, causing widespread mortality of organisms and a mass stranding event, with fish being one of the most affected groups (Hernández-Miranda et al 2010, 2012b. These authors reported a recovery in richness of the fish assemblage in a timescale of only 3 months; nevertheless, densities reached only about half their previous level after 2 years of the event.…”
Section: Discussionmentioning
confidence: 93%